Evaluacion de tecnicas de propagacion de Mammillaria oteroi Glaá R. Foster - Martinez Mendoza, D.=700 1 Lopez Rodriguez, F.M.; Flores martinez, A.; Manzanero Medina, G.I.
(En, Es)
ilus., 9 ref.
Keywords: CLONES; GERMINACION; CACTACEAE; PROPAGACION; MEXICO; MAMMILLARIA OTEROI